The bail-out!: Positive political economics of Greek-type crises in the EMU - Christian Fahrholz; Cezary Wojcik (Center for Social and Economic Research (CASE), 2010)
The Greek bail-out was highly controversial. An oft-heard assessment is that i) the bail-out was a mistake, ii) the political haggling over it was irrational and iii) the bail-out will create a moral hazard problem. Contrary to this view, our analysis suggests that, given EMU's present political-economic set-up, i) the bail-out was unavoidable, ii) the lengthy process of political haggling leading to it was understandable, and iii) the bail-out does not have to be necessarily associated with a future moral hazard problem. Based on our analysis, we suggest that the EMU's institutional design could be improved by establishing "exit rules" and that bail-outs should be made rule-based. We have based our analysis on a politicaleconomic, game-theoretic model that helps to understand why and how the parties involved in the Greek crisis arrived at the bail-out and on what conditions the final solution depended. The model allows tracing analytically the dynamics of the negotiation processes as well as the conditions and parameters on which the scope and limits of fiscal redistribution in EMU depends. In doing so, we formally take account of the "negative externality" problem that has been central to policy debates related to the EMU's institutional design and has played an important role in the Greek crisis. However, contrary to the existing literature, we do not only focus on the economic aspects of such negative externality, but also look at where they emanate from and interact with political factors, in particular the dynamics of the political negotiation process within the EMU
Keywords: E62; F33; H77; C70; 330; Greek crisis; bail-out; negative externality; political economics; game theory; euro; EMU; Öffentliche Schulden; Staatsbankrott; Schuldenübernahme; Griechenland; Eurozone; Verhandlungen; Neue politische Ökonomie; Spieltheorie; EU-Staaten